Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1063/1.857876
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic geometric properties of scalar interfaces in turbulent jets

Abstract: Experiments were conducted in which the behavior of scalar interfaces in turbulent jets was examined, using laser-induced fluorescence (LIF) techniques. The experiments were carried out in a high Schmidt number fluid (water), on the jet centerline, over a jet Reynolds number range of 1000 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
57
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 18 publications
12
57
0
Order By: Relevance
“…2a). It is a smoothly-increasing function of scale, bounded by its limiting value of unity (topological dimension), at the smallest scales, and 2 (embedding dimension), at the largest scales (cf., also, Miller & Dimotakis 1991). A similar behavior obtains for lower and higher values of the scalar threshold.…”
Section: Isoscalar Geometry In Turbulent Jetssupporting
confidence: 56%
See 1 more Smart Citation
“…2a). It is a smoothly-increasing function of scale, bounded by its limiting value of unity (topological dimension), at the smallest scales, and 2 (embedding dimension), at the largest scales (cf., also, Miller & Dimotakis 1991). A similar behavior obtains for lower and higher values of the scalar threshold.…”
Section: Isoscalar Geometry In Turbulent Jetssupporting
confidence: 56%
“…for a coverage count normalized at λ = δ, i.e., for N d (δ) = 1 (Takayasu 1982(Takayasu , 1992Miller & Dimotakis 1991;Dimotakis 1991;and Catrakis & Dimotakis 1996a). A more complete discussion of these notions can be found in the review by .…”
Section: Fractals and Scale-dependent Irregular Level Setsmentioning
confidence: 99%
“…In contradiction to Batchelor's 19 prediction, several experimental studies of high Schmidt number turbulent scalars have not observed the κ −1 scaling behavior. [20][21][22][23] Some observed that a weaker scaling, possibly a lognormal scaling, across the viscous-convective subrange may be more representative of experimental data. 20 Case 5 has a sufficiently high Sc = 256 to allow for a comparison of the scalar spectra produced by the linear scalar and mean gradient forcing methods to both Batchelor's 19 predictions and the summarized experimental results.…”
Section: -15mentioning
confidence: 99%
“…These differences are more pronounced at larger Sc and can be considered in terms of Batchelor's theory for scalar behavior 19 and experimentallyobserved high-Schmidt number scalar behavior. [20][21][22][23] …”
Section: Implications For High-schmidt Number Scalar Mixingmentioning
confidence: 99%
“…Certain experiments and simulations support the scaling, [2][3][4][5] whereas others contradict it. [6][7][8] There even exist certain theoretical objections to the κ −1 scaling, based on the requirement of boundedness of the scalar variance.…”
Section: Introductionmentioning
confidence: 99%